2017
DOI: 10.1002/term.2479
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chemical immobilization of SDF-1α into muscle-derived scaffolds on angiogenesis and muscle progenitor recruitment

Abstract: The availability of three-dimensional bioactive scaffolds with enhanced angiogenic capacity that have the capability to recruit tissue specific resident progenitors is of great importance for the regeneration of impaired skeletal muscle. Here, we have investigated whether introduction of chemoattractant factors to tissue specific extracellular matrix promotes cellular behaviour in vitro as well as muscle progenitor recruitment and vascularization in vivo. We developed an interconnective macroporous sponge from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 67 publications
(97 reference statements)
0
13
0
Order By: Relevance
“…Review over protein presentation in vivo compared to physical encapsulation. 45,46 Covalent conjugation strategies are valuable in situations where long-term protein presentation is necessary to elicit a sustained cellular response in vivo. Protein immobilization is often achieved using amine-reactive chemistry, which requires an amine group available for nucleophilic attack, or carboxyl-reactive chemistry, which requires a carboxyl group for electrophilic attack.…”
Section: Biomaterials Sciencementioning
confidence: 99%
“…Review over protein presentation in vivo compared to physical encapsulation. 45,46 Covalent conjugation strategies are valuable in situations where long-term protein presentation is necessary to elicit a sustained cellular response in vivo. Protein immobilization is often achieved using amine-reactive chemistry, which requires an amine group available for nucleophilic attack, or carboxyl-reactive chemistry, which requires a carboxyl group for electrophilic attack.…”
Section: Biomaterials Sciencementioning
confidence: 99%
“…While the SDF‐1α releasing hydrogel was able to restore blood perfusion, the collagen hydrogel without SDF‐1α showed similar results. SDF‐1α has also been chemically immobilized onto a muscle derived decellularized ECM (dECM) sponge 103 . When implanted into muscle, the sponges with immobilized‐ SDF‐1α increased vessel density and size compared to adsorbed‐ SDF‐1α sponges or blank sponges.…”
Section: Release Of Bioactive Moleculesmentioning
confidence: 99%
“…Moreover, implantation of this sponge scaffold in the rat femoral muscle increased neovascularization, infiltration of host Pax7+, and CXCR4+ cells toward the sponge. (Rajabi et al 2018). Alvarez Fallas et al demonstrated that acellular muscle ECM preserved pro-angiogenic protein, such as HGF, VEGF, and SDF-1α.…”
Section: Scaffold Design For Enhanced Vascularizationmentioning
confidence: 99%